2017
DOI: 10.18632/oncotarget.20603
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of 137Cs irradiation on pharmacological stimulation of reactive oxygen species in hippocampal slices from apoE2 and apoE4 mice

Abstract: In humans, apoE, which plays a role in repair, is expressed in three isoforms: E2, E3, and E4. E4 is a risk factor for age-related cognitive decline (ACD) and Alzheimer's disease (AD), particularly in women. In contrast, E2 is a protective factor for ACD and AD. E2 and E4 might also differ in their response to cranial 137Cs irradiation, a form of radiation typically used in a clinical setting for the treatment of cancer. This might be mediated by reactive oxygen species (ROS) in an-apoE isoform-dependent fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…1 However, emerging data have shown that the APOE e4 allele increases neurodegeneration mediated by tau 40 and α-synuclein [4][5][6] protein and promotes neuroinflammation 41 and oxidative stress. [42][43][44] Furthermore, the APOE e4 allele has reduced efficiency in brain homeostatic pathways, including lipid transport, glucose metabolism, and cerebrovascular function. 1 Such amyloid-unrelated effects may also negatively influence cognition in patients with PD, although this possibility requires further assessment and validation.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, emerging data have shown that the APOE e4 allele increases neurodegeneration mediated by tau 40 and α-synuclein [4][5][6] protein and promotes neuroinflammation 41 and oxidative stress. [42][43][44] Furthermore, the APOE e4 allele has reduced efficiency in brain homeostatic pathways, including lipid transport, glucose metabolism, and cerebrovascular function. 1 Such amyloid-unrelated effects may also negatively influence cognition in patients with PD, although this possibility requires further assessment and validation.…”
Section: Discussionmentioning
confidence: 99%
“…The brain is vulnerable to oxidative damage because of its high oxygen consumption and relatively low levels of antioxidants [35]. Moreover, the high concentration of unsaturated fatty acids in the brain makes this tissue a proper substrate for the occurrence of peroxidation reactions [22,36].…”
Section: Introductionmentioning
confidence: 99%